(untitled) (Research, Society and Development, 2019)
This article aims to present the Semantic Panel as an innovative didactic resource in the teaching context. The objective of this study was to present the Semantic Panel, design methodological technique of design, as didactic resource applied in a group of higher education students of a private teaching institution located in the city of Santa Maria, RS. The type of research carried out in this study is a qualitative research-action. The results of the study indicated that the application of the semantic panel as a didactic resource made possible the relation between theory and practice, the ability to plan, create, develop potentialities, expose, discuss and reflect group ideas, as well as motivation and involvement of students to develop the proposed activity. It is concluded that to promote innovation in the classroom through practical didactic resources through generating themes are part of a proposal of creative teaching, which can draw the attention of the students to the contents studied in the classroom, since it is given space for them to develop, so they can become more critical and protagonists of their teaching-learning process in the classroom.